Estudo da modificação superficial de fibras de carbono por meio de tratamentos a plasma para o aumento da adesão na interface de compósitos fibra de carbono/PPS - Santos, Alberto Lima [UNESP] (2015)
In this it has been carried out the processing of thermoplastic composites obtained from carbon fibers (CF) treated by plasma assisted techniques. The employed treatments were Dielectric Barrier Discharge (DBD) that is performed in atmospheric pressure, involving low energy and Plasma Immersion Ion Implantation (PIII), which is held in low pressure regime, consisting of higher energies. After these treatments, both treated and untreated samples, were characterized. A comparison of the results was carried out to determine which treatment is most effective to achieve better physico-chemical properties on the fibers to obtain thermoplastic composites, which were produced by hot compression molding. Several characterization techniques were employed, such as scanning electron microscopy (SEM), atomic force microscopy (AFM), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction, and some mechanical tests of the composites, such as interlaminar shear strength (ILSS) and dynamic mechanical analysis (DMA). After analyzing the results, it was verified that the DBD and PIII treatments are effective tools for improving the adhesion of the carbon fiber/polymeric matrix interface, due to the CF roughness increasing and the introduction of polar groups on the carbon fiber surface. Additionally, it was noticed an increase of composites shear strength that were produced with treated carbon fibers (DBD and PIII)